Sudden Sensorineural Hearing Loss in patient with Chronic Myelogenous Leukemia - A case study - Aremu Shuaib Kayode; Ibijola AA; Dosunmu Adepeju Oluwatona (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
Rapid progressive sensorineural hearing damage as the early sign of a hematological illness is often found in patients with Chronic Myeloid Leukemia. A 100-year- old man presented to our outpatient department with 2 hours history of bilateral sudden sensorineural hearing loss (SSNHL). After the hematological, bone marrow and radiological workup, the patient was found to have chronic myelogenous leukemia. The patient was identifi ed as having unexplained SSNHL and was admitted for treatment, but his hematological investigations indicated that he had an undiagnosed form of leukemia. The possible pathogenesis of developing SSNHL from CML is discussed here within the report with highlights of differential diagnosis of SSNHL.